Integrating Climate Resilience in Value Chains: practical examples - Daniels, Stephanie (2018)
The presentation Integrating Climate Resilience in Value Chains: practical examples is by Stephanie Daniels from the Sustainable Food Lab. Presented at the WBCSD Climate Smart Agriculture workshop at the University of Vermont, Burlington, VT on 27 March 2018.